93.5k views
0 votes
Please HELP me I need it :)

Please HELP me I need it :)-example-1
User Mandreko
by
5.1k points

2 Answers

3 votes

Answer:

C

Explanation:

Note that if x = h is a root of a polynomial f(x) then f(h) = 0

Note the sum of the coefficients of the given polynomial

x³ + 4x² + x - 6 is

1 + 4 + 1 - 6 = 0

Hence x = 1 is a root( zero) and (x - 1) is a factor

User Charon
by
5.2k points
3 votes
The answer is C. 1

You can just plug in the different answers for x and see which one equals zero.

F(1) = 1 + 4 + 1 - 6 = 0
User RizkiDPrast
by
4.5k points